Regional growth and finance in Europe: is there a quality effect of bank efficiency? - Iftekhar Hasan; Michael Koetter; Michael Wedow (Bank of Finland, 2009)
In this study, we test whether regional growth in 11 European countries depends on financial development and suggest the use of cost- and profit-efficiency estimates as quality measures for financial institutions. Contrary to the usual quantitative proxies for financial development, the quality of financial institutions is measured in this study as the relative ability of banks to intermediate funds. An improvement in bank efficiency spurs five times more regional growth than does an identical increase in credit. More credit provided by efficient banks exerts an independent growth effect in addition to the direct quantity and quality channel effects.
URN:NBN:fi:bof-20140807560
Keywords: G21; O16; O47; O52; 330; bank performance; regional growth; bank efficiency; Europe